Bee a Good Human A Pollinators' Guide to a Better Life. - Beckman, Ali (Red Lightning Books, 2021)
- Instagram fanbase (@SoFlyTaxidermy) is over 162K and growing with famous fans - Features over 100 comics, about 20% never seen before - Combines humor, self-love, and the importance of pollinators - Author is eager to promote and is glad to use her more well-known followers to make a splash.